The imperial cult in the Latin West : studies in the ruler cult of the western provinces of the Roman Empire. Vol. 3, Provincial cult. Part 1, Institution and evolution - Fishwick, Duncan, 1929- (Religions in the Graeco-Roman World, 2002)
This volume deals with the institution and evolution of imperial cult at the provincial level from the earliest foundations under Augustus down to the mid-third century A.D. On the basis of detailed examination of evidence from the different regions or provinces of the Latin west the emphasis of provincial cults can be seen to move first from the living emperor and Roma to the deified emperor, then from a composite cult of living and deified dead emperors to a renewed emphasis on the reigning emperor in the late second and early third centuries. Analysis is based primarily on the study of epigraphical, numismatic and iconographic evidence, generously illuminated by plates. The volume concludes with a series of essays summarizing the main lines of development in the light of various related issues.